Analysis of Merdeka Curriculum Learning Planning in Senior High School - Rostini, Deti; Sriyanti, Ika; Nurhidayah, Nurhidayah; Budiman, Isep (FKIP - Universitas Riau, 2026)
The implementation of the Merdeka Curriculum in high schools’ places teaching modules as the heart of student-centered learning planning. However, there is still a gap between the principles of the curriculum and the quality of the planning made. This study is to analyze the learning planning in the Merdeka Curriculum in high school, focusing on the suitability of the teaching modules with the principles of flexibility, meaningful learning, and student characteristics. The research uses a literature study method. Primary data in the form of a high school Pancasila Education teaching module was analyzed textually evaluating its structure, content, and suitability with the learning outcomes of the Merdeka Curriculum, supported by secondary data sources such as policy and academic literature. Effective teaching modules serve as strategic instruments that bridge policy and practice. The module has a systematic structure (general information, core components, appendices) that supports consistency between objectives, materials, methods, and assessments. The integration of contextual approaches such as models, dimensions, and digital technologies creates relevant and inclusive learning. The Merdeka Curriculum teaching module is a holistic and transformative planning tool.